Genetic Diversity among Single, Double, And Triple Cross Hybrids in Beit Alpha Cucumber (Cucumis sativus) - Altamari, Adel M.; Akash, Muhanad W.; Kasrawi, Mahmoud A. (Jordan Journal of Agricultural Sciences, 2022)
Genetic variation was investigated in fifteen single, eighteen three-way, and nine double hybrid crosses and their parents along with nine elite commercial cucumber hybrids. Six lines (NS5, NS9, NS17, NS29, NS31, and NS33) were used to develop these cross hybrids. Based on AFLP and SSR analysis, the studied cucumber genotypes have a narrow genetic base. The results also showed genetic differentiation compared to commercial varieties. Out of 1352 bands produced from 12 AFLP primer pairs, only 47 were polymorphic. Similarly, out of 26 SSR primers, only one primer was polymorphic. The highest heterozygosity index (0.6044), polymorphic information content value (0.5392), and marker Index (0.6044) were observed with M-CTT_E-AAG AFLP primer combination, while the highest effective multiplex ratio (2.8246) and resolving power (4.8421) were observed with M-CTC_E-AGC AFLP primer combination. Genetic distance estimation revealed clear distinctiveness of the studied genotypes with the control varieties. The cluster analysis by UPGMA showed two main clusters covering 84% of the studied genotypes grouped. This research shows that double and three-way hybrid crosses can be used in cucumber hybrid breeding.